Legal GAP antara Pemilik Tanah dan Aparat Menimbulkan Sengketa dalam Pengadaan Tanah Untuk Kepentingan Umum (Studi Kasus di Bengkulu) - Yanto Sufriadi (Fakultas Hukum Universitas Islam Indonesia, 2013)
The research focuses on the legal definition of land procurement for public use that caused many disputes in the past. The problem studied here is the understanding on public interest, land rights, and proper indemnification of the land owners and the land procurement acting authorities. This research is qualitative research with socio legal approach using constructivism paradigm. The research used data from field study and literature study. The findings conclude that the dispute on the land procurement for public use was caused by injustice because of legal understanding gap between the land owners who viewed law as traditions and values prevailing in society and the land procurement acting authorities who viewed law in form of regulations which was comprehended only in formal-textual context.